A framework for experience management in public organisations - Lambert, Simon C.; Arenas, Alvaro Enrique; Miles, Alistair J. (Revista Colombiana de Computación, 2005)
The Pellucid project developed an adaptable and customisable platform for enabling experience management in public organisations. A framework for experience management has been developed based on the generation of ‘active hints’ that are presented to the user according to working context. Working context encompasses both position in the work process and domain-specific characteristics. The paper presents this framework and describes the engineering process that was undertaken following the CommonKADS methodology. Keywords: Knowledge Management, Experience Management, E-Government, Workflow Management Systems, CommonKADS.